Polycystic ovary syndrome in a virilised, premenarcheal girl. Issue 9 (September 1989) - Clarke, C F; Piesowicz, A T; Edmonds, K; Grant, D
Abstract : A premenarcheal girl aged 12 years presented with an abdominopelvic mass and virilisation. A large ovarian cyst was removed at laparotomy. A histological diagnosis of polycystic ovarian syndrome was made, with no evidence of an associated masculinising tumour.